Интродукция видов рода Sorbus L. в Донецкий ботанический сад НАН Украины - Дацько, А.М. (Промышленная ботаника, 2004)
Introductional trial of the genus Sorbus species at the Donetsk Botanical Gardens is considered. Results of the species inventary in 2003 are presented. Estimation of introduction successfulness of mountain ashes growing in the territory of the Donetsk Botanical Gardens is given.